Increased Fear-Potentiated Startle in Major Depressive Disorder Patients with Lifetime History of Suicide Attempt - Ballard, Elizabeth D. (2014)
BACKGROUND: Suicide is a common reason for psychiatric emergency and morbidity, with few effective treatments. Anxiety symptoms have emerged as potential modifiable risk factors in the time before a suicide attempt, but few studies have been conducted using laboratory measures of fear and anxiety. We operationally defined fear and anxiety as the increased in startle reactivity during anticipation of predictable (fear-potentiated startle) and unpredictable (anxiety-potentiated startle) shock. We hypothesized that a lifetime history of suicide attempt (as compared to history of no suicide attempt) would be associated with increased fear-potentiated startle. METHODS: A post-hoc analysis of fear- and anxiety-potentiated startle was conducted in 28 medication-free patients with Major Depressive Disorder (MDD) divided according to suicide attempt history. RESULTS: The magnitude of fear-potentiated startle was increased in depressed patients with lifetime suicide attempts compared to those without a lifetime history of suicide attempt (F(1,26) = 5.629, p = .025). There was no difference in anxiety-potentiated startle by suicide attempt history. LIMITATIONS: This is a post-hoc analysis of previously analyzed patient data from a study of depressed inpatients. Further replication of the finding with a larger patient sample is indicated. CONCLUSIONS: Increased fear-potentiated startle in suicide attempters suggests the role of amygdala in depressed patients with a suicide attempt history. Findings highlight the importance of anxiety symptoms in the treatment of patients at increased suicide risk.